1998
DOI: 10.1097/00005176-199811000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Gluten-Free Diet: A Nutritional Risk Factor for Adolescents with Celiac Disease?

Abstract: In people with celiac disease, adherence to a strict gluten-free diet worsens the already nutritionally unbalanced diet of adolescents, increasing elevated protein and lipid consumption. In the follow-up of patients with celiac disease, considerable effort has yet to be made to improve compliance with a gluten-free diet, and especially to control the nutritional balance of the diet in compliant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
193
4
16

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(229 citation statements)
references
References 15 publications
16
193
4
16
Order By: Relevance
“…However, antibody tests might not reveal slight dietary transgressions [25] . In the present experience, the Biocard test recognized the disappearance of anti-tTG antibodies in all the patients with a GFD compliance and was positive in 14% (6/43) of the patients who admitted transgressions: they were young patients (median age 24 years), confirming the reports that adolescents had difficulties adhering strictly to the diet [26][27][28] . The positivity of the test presumes major dietary transgressions [25] .…”
Section: Discussionsupporting
confidence: 86%
“…However, antibody tests might not reveal slight dietary transgressions [25] . In the present experience, the Biocard test recognized the disappearance of anti-tTG antibodies in all the patients with a GFD compliance and was positive in 14% (6/43) of the patients who admitted transgressions: they were young patients (median age 24 years), confirming the reports that adolescents had difficulties adhering strictly to the diet [26][27][28] . The positivity of the test presumes major dietary transgressions [25] .…”
Section: Discussionsupporting
confidence: 86%
“…GFD seems to increase the risk of overweight or obesity, and concerns have been raised about the nutritional imbalance and hypercaloric content of commercial or natural gluten-free food. There is a trend, both in adults and in children, on a GFD to replace gluten-derived carbohydrates with an increased consumption of fats, proteins and hypercaloric beverages and to decrease fiber intake (Mariani et al, 1998;Dickey and Kearney, 2006;Ferrara et al, 2009). Incorrect dietary habits can be induced by unpalatability and expense of commercial gluten-free products or by the availability of commercial gluten-free snacks and biscuits with a high content of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect dietary habits can be induced by unpalatability and expense of commercial gluten-free products or by the availability of commercial gluten-free snacks and biscuits with a high content of lipids. Adolescents are likely to be at a higher risk of inappropriate and potentially harmful alimentary habits (Mariani et al, 1998). Dietary modifications are more troublesome in countries such as Italy, where people have a high gluten-containing diet (bread, pizza and pasta), but similar dietary imbalances have also been described in Dutch children with CD (Hopman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mariani et al first reported high prevalence of overweight and obesity in CD adolescents on a gluten-free diet (GFD). 2 The risk of overweight and obesity at diagnosis of CD varies largely with the nutritional status of the underlying population, as suggested by some very recent pediatric papers.…”
Section: Introductionmentioning
confidence: 98%